2011
DOI: 10.1088/0004-637x/733/1/54
|View full text |Cite
|
Sign up to set email alerts
|

Disk Formation in Magnetized Clouds Enabled by the Hall Effect

Abstract: Stars form in dense cores of molecular clouds that are observed to be significantly magnetized. A dynamically important magnetic field presents a significant obstacle to the formation of protostellar disks. Recent studies have shown that magnetic braking is strong enough to suppress the formation of rotationally supported disks in the ideal MHD limit. Whether non-ideal MHD effects can enable disk formation remains unsettled. We carry out a first study on how disk formation in magnetic clouds is modified by the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
119
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(128 citation statements)
references
References 25 publications
9
119
0
Order By: Relevance
“…This poses further problems to disk formation in previous numerical studies of collapse and disk formation. On the other hand, the inclusion of the Hall effect does not require a rotating envelope core to form a rotating structure (e.g., Krasnopolsky et al 2011;Li et al 2011). Further studies are required to compare the expected observables from rotating and non-rotating models.…”
Section: On the Large-scale Rotationmentioning
confidence: 99%
“…This poses further problems to disk formation in previous numerical studies of collapse and disk formation. On the other hand, the inclusion of the Hall effect does not require a rotating envelope core to form a rotating structure (e.g., Krasnopolsky et al 2011;Li et al 2011). Further studies are required to compare the expected observables from rotating and non-rotating models.…”
Section: On the Large-scale Rotationmentioning
confidence: 99%
“…In the simplest case of electron-ion-neutral fluid, the spinup is caused by the current carriers (the electrons) moving in the azimuthal direction, generating a magnetic torque through field twisting; the toroidal current is produced by gravitational collapse, which drags the poloidal field into a pinched, hourglass-like configuration. The Hall spinup was studied numerically by Krasnopolsky et al (2011) and semi-analytically by Braiding & Wardle (2012a,b). Krasnopolsky et al (2011) showed that a rotationally sup-ported disk can form even in an initially non-rotating core, provided that the Hall coefficient is large enough.…”
Section: Non-ideal Mhd Effectsmentioning
confidence: 99%
“…Magnetic fields are also believed to be of key importance during the star-formation process (Hennebelle & Fromang 2008;Hennebelle & Ciardi 2009;Commerçon et al 2010;Hennebelle et al 2011;Seifried et al 2011;Joos et al 2012). Even if diffusion is required to remove much of the magnetic flux during that process (Mellon & Li 2009;Krasnopolsky et al 2010Krasnopolsky et al , 2011Li et al 2011;Santos-Lima et al 2012;Dapp et al 2012), it is plausible that some net poloidal flux is retained and carried down to the scale of the disk during its formation. The resulting strength of that potential magnetic field is highly uncertain, but might be in the approximate range 10 −2 to a few Gauss (Wardle 2007).…”
Section: Introductionmentioning
confidence: 99%